Potential Risk Factors for Down Syndrome in Libya - Fahima A. Al-Nagar; Mansur E. Shmela; Entisar A. Elgmati; Fauzia M. Mohamed; Abdulmaula M. Abogrein; Nuri M. Alkhder; Amnnah E. Buthaynah (African Journal of Advanced Pure and Applied Sciences, 2026)
Down syndrome (DS) is a genetic condition of the live-born with an extra full or partial copy of chromosome 21. This extra genetic material has been linked to several risk factors. Some parents have a higher risk of having a child with DS. The current study aimed to evaluate the effect of potential risk factors for DS in Libya. This questionnaire-based study was conducted from September 2022 to December 2022 in different DS centers in Tripoli. One hundred fifty Libyan families (mother, father, and DS child) participated in the study. Data about demographic and health characteristics of the DS children and parental information about potential risk factors for having a DS child was obtained from questionnaires. The study findings indicated that higher parity and parental body mass index were important risk factors associated with DS. Additionally, based on descriptive statistics, maternal folic acid intake before pregnancy was low. Nevertheless, factor analysis results highlighted the fact that the risk of DS is multifactorial, with important contributions from parental age and birth order, parental health and medication use, genetic and environmental exposure, reproductive health and parental obesity. In conclusion, several risk factors for DS were identified in Libya, emphasizing the multifactorial nature of the condition.